Sovereign Default, Enforcement and the Private Cost of Capital - Andreasen, E (Elsevier Inc., 2015)
This paper develops a signaling model for a small open economy in which the government s sovereign debt repayment decision gives lenders new information regarding the state s capacity to enforce contracts. Contract enforcement affects the expected repayment of private loans. Therefore, if lenders receive negative information from the sovereign default about the state s capacity to enforce contracts, they worsen the financial conditions offered to local firms, triggering a sharp reduction in credit and investment. The key contribution of this paper is to rationalize the worsened private-sector financial conditions observed after default episodes by modeling the price effect of the informational channel. © 2015 Elsevier Inc.